THE RELATIONSHIP BETWEEN INSTRUCTIONAL SUPPORT, PEER SUPPORT, AND STUDENT SATISFACTION ON ENTERPRISE RESOURCE PLANNING - Lita Kusumasari; Badr Alsolami (LPPM STIE YKPN Yogyakarta, 2024)
Business needs enterprise resource planning (ERP). SAP is the market leader of ERP. Due the importance of ERP in business, higher education implements in curriculum. that require internal cross-disciplinary coordination. Students must acquire and understand cross functional business processes while implementing the SAP software. It is challenging for students to be successful in this class. Based on the conditions, the purpose of study is finding the effect of instructor support and peer support toward student satisfaction. This is quantitative research. The research design is collecting primary data using online survey for students. There were 104 students as respondents. The students conduct ERP class by hybrid, online and offline methods. SPSS was used to analyse data using multiple regression. Data was running for validity and reliability test. The result is data could analyse further for the model. Based on F test, the model fits. Regression analysis indicated that instructor support and peer support are positively related to student satisfaction. This study demonstrated the importance for building support for student satisfaction. The result aligned with prior studies.